Housekeeping Strategy and Its Impact on Room Occupancy at Parlezo Hotel Labuan Bajo - Mappiasse, Mappiasse; Hehanussa, Akib; Hanggu, Elizabeth Oktaviani; Sari, Indra Ratna; Adi Saputri, Luh Gede Elvina (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study examines the strategic role of the housekeeping department in increasing room occupancy at Parlezo Hotel, Labuan Bajo. Employing a qualitative descriptive approach, data were collected through interviews, observations, documentation, and internal occupancy reports from 2023–2024. Fieldwork was conducted over a two-month period (November–December 2024) and involved five informants, including one housekeeping supervisor and four housekeeping staff. The findings reveal that personalized services—such as towel art for returning guests, birthday surprises, and extra amenities for long-stay visitors—play a key role in enhancing guest satisfaction and loyalty. Infrastructural limitations, such as the absence of an elevator, are mitigated through empathetic service and real-time room coordination using GuestPro, a cloud-based Property Management System (PMS). Operational efficiency is further supported by structured task delegation, regular briefings, quality assurance routines, and responsive communication. Notably, the occupancy rate increased by 5.82% from 2023 to 2024, with a two-year average of 77.19%, reflecting the effectiveness of targeted housekeeping strategies. The study concludes that a well-trained and strategically coordinated housekeeping team is instrumental in maintaining service excellence and improving hotel performance in a competitive tourism environment.